Evaluating the Impact of Customer Demographical Characteristics on Relationship Outcomes - Teresa Fernandes (2013)
This study investigated the impact of customer demographic characteristics on relationship outcomes. Through exploratory factor analysis and multiple analysis of variance, the empirical findings demonstrated that customer age and gender were effective discriminators of relationship marketing outcomes. As proposed, the findings show that young and female customers are more likely to be loyal and to spread positive word-of-mouth than other market segments. In addition, the findings depict a high degree of consistency in relationship outcomes regardless of educational background. Since there is a notable absence of literature that assesses the impact of demographics on relationships in marketing, particularly in a service context, this research adds significant value. The study also offers empirical insights on segmentation and positioning of relationship marketing strategies by identifying relationship prone individuals based on their personal characteristics.